Preliminary observations of a natural eye ointment from Curcuma aromatica to treat goat keratoconjunctivitis and uveitis - K. Shankar Ganesh (2020)
The livestock industry has been relying merely on chemically synthesised antibiotic for eye infections as sprays and ointment. A natural remedy from Curcuma spp. has been tested for efficacy in curing keratoconjunctivitis and uveitis. A severe case of uveitis was cured within 7 days, with impaired vision restored. These results were observations of a preliminary study conducted in a goat with uveitis.